Measuring physical demand in Augmented Reality learning environments. - Pulipati, Varun; Kim, Jung Hyup; Wang, Fang; Oprean, Danielle; Seo, Kangwon (Ergonomics, 2025)
Augmented Reality revolutionises education by enhancing learning with interactive, immersive experiences. However, the impact of long-term AR use, particularly in terms of physical demand, within educational environments remains poorly understood. This study investigates the relationship between AR engagement and physical demand, utilising motion capture technology, NASA Task Load Index, and HoloLens eye-tracking to quantify user posture, engagement, and perceived workload. We hypothesise that prolonged AR interaction results in a change in slouching scores, indicating increased fatigue. The results show a strong correlation between the slouching score and the NASA-TLX physical demand score. Our study lays the groundwork for incorporating predictive modelling to develop proactive physical demand measures. Practitioner Summary: Measuring physical demand during AR-based learning is possible using the slouching score. This metric enables dynamic assessment of user physical demand in AR environments, paving the way for improved AR system design to minimise physical fatigue during tasks or learning, enhancing overall user comfort and performance.